Pengaruh Kosentrasi NaOH Dan Jumlah Grafena Oksida Pada Geopolimer Berbasis Limbah Fly Ash Pabrik Kelapa Sawit - Gilang Fathurrahman; Amun Amri; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Geopolymers are the result of synthesizing inorganic polymers by reacting high concentrated alkali solutions with Si and Al minerals contained in fly ash. The use of these geopolymers can reduce consumption levels of OPC use in the construction industry. This study aims to create geopolymer based fly ash palm mill with the addition of graphene oxide as filler and Determine the effect of NaOH concentration and the amount of grafena oxide addition to geopolymer compressive properties as well as to study the morphological and physical-chemical structure in geopolymer. Geo-polymer preparation includes several steps of fly ash and sand preparation and then continued by making alkali activator solution (NaOH + Sodium silicate) with 6 M, 10 M and 14 M variations and grafena oxide addition with 0%, 0.2% wt, 0.4% wt, and 0.6% wt. The results showed that the highest compressive strength on the addition of NaOH concentration of 14 M and the addition of 0.6% wt of oxena oxide is 13.2 Mpa on and the lowest compressive strength is produced at the concentration of NaOH 6 M and without the addition of GO that is 5.1 Mpa. This study shows that the addition of graphene oxide can increase the compressive strength of the geopolymer and NaOH as an alkaline solution can reduce the GO sheet into rGO sheets and create an increasingly denser geopolymer structure as the NaOH concentration increases.Key words : Geopolymer, Fly Ash, Graphene Oxide